Development of an evaluation framework for African–European hospital patient safety partnerships. Issue 4 (13th November 2013) - Rutter, Paul; Syed, Shamsuzzoha B; Storr, Julie; Hightower, Joyce D; Bagheri-Nejad, Sepideh; Kelley, Edward; Pittet, Didier
Abstract : Background: Patient safety is recognised as a significant healthcare problem worldwide, and healthcare-associated infections are an important aspect. African Partnerships for Patient Safety is a WHO programme that pairs hospitals in Africa with hospitals in Europe with the objective to work together to improve patient safety. Objective: To describe the development of an evaluation framework for hospital-to-hospital partnerships participating in the programme. Methods: The framework was structured around the programme's three core objectives: facilitate strong interhospital partnerships, improve in-hospital patient safety and spread best practices nationally. Africa-based clinicians, their European partners and experts in patient safety were closely involved in developing the evaluation framework in an iterative process. Results: The process defined six domains of partnership strength, each with measurable subdomains. We developed a questionnaire to measure these subdomains. Participants selected six indicators of hospital patient safety improvement from a short-list of 22 based on their relevance, sensitivity to intervention and measurement feasibility. Participants proposed 20 measures of spread, which were refined into a two-part conceptual framework, and a data capture tool created. Conclusion: Taking a highly participatory approach that closely involved its end users, we developed an evaluation framework and tools to measure partnership strength, patient safety improvements and the spread of best practice.